Meningkatkan Sikap Positif Terhadap Perilaku Tidak Merokok dan Kecenderungan untuk Berhenti Merokok Melalui Pelatihan - T. Cut Lizam, Yayi Suryo Prabandari, Amitya Kumara (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Almost everybody knows that smoke could endangered smoker’s health and people surrounding (passive smoker). The influence of peer, self appearance, curiosity, stress, boring, masculinity and rebelience are some of major issues that could contribute teenagers to start smoking. Therefore, health education is needed to improve positive attitude toward non smoking behavior and tendency to quit smoking by empowering their own emotional through emotional intelligence training.Objective: This research was aimed to find out the influence of training on emotional intelligence in order to improve positive attitude toward non smoking behavior and tendency to quit smoking in intervention group and the difference on attitude as well as intention to quit smoking in intervention group with control group.Method: Quasi experimental study was conducted with pre-test and post-test with control design. Experiment group was given training on emotional intelligence with lecture method and sensitivity training. The research subjects were 43 in intervention group and 41 in control group with research population was boys who smoke in grade II of social science majoring class. Data analysis was conducted with paired t-test for one group and independent t-test in different group with significance level of 5% or p<0.05.Result: There was a significant positive improvement on attitude toward non smoking behavior especially in pretest and posttest-1, pretest and posttest 2 (p<0.05) and there was an improvement on tendency to quit smoking in intervention group. There was a significant difference (p<0.05) on attitude in intervention and control groups. Furthermore, there was not an improvement on positive attitude toward non smoking behavior in intervention group especially in the indicator of self motivation and in posttest 1 and posttest 2.Conclusion: Health education through training on emotional intelligence could improve positive attitude toward non smoking behavior and tendency to quit smoking in teenager.Keywords: training on emotional intelligence, attitude toward smoking and tendency to quit smoking